(untitled) (Global Journal of Science Frontier Research, 2017)
This paper deals with the distribution of natural waves of an infinite cylinder with radial crack and wedge. The task is put in cylindrical coordinates. Viscoelastic cylinder with radial crack is a limiting case of the wedge with an angle 0 360 . With the help of the Navier equations and physical system received six differential equations. After not complicated conversion obtained spectral boundary value problem for systems of ordinary and partial differential equations complex the coefficient, which is then solved by the direct and orthogonal shooting with a combination of the method of Mueller on a complex arithmetic. A dispersion relation for a cylinder with radial crack and the wedge was got.